Sensorless vector control of Dual Star induction Motor Associated with Fuzzy Mutual-MRAS estimator in electric vehicle - Ismail BENMILOUD; Katia KOUZI; Aissa AMEUR (Revista Română de Informatică și Automatică, 2023)
Sensorless control has become an attractive and important topic from an industrial perspective. The presence of sensors in electronic speed drives can reduce their robustness and reliability while increasing costs and mounting complexity. Therefore, mechanical sensors will be replaced by a calculation algorithm that provides speed estimation from the electrical terminal of the machine. It is imperative that the performance required from this estimator be close to or similar to that provided by a physical sensor. In this paper, different estimation and observation techniques will be presented. Then, Sensorless vector control based on a mutual – MRAS estimator and Fuzzy mutual – MRAS estimator for Dual Star induction Motor (DSIM) to estimate the speed, as well as the resistances for both the stator and rotor will be introduced. Finally, the results of the simulation will be shown and discussed.